Mesenteric lymph node cells from neonates present a prominent IL-12 response to CpG oligodeoxynucleotide via an IL-15 feedback loop of amplification - Ferret-Bernard, Stéphanie (BioMed Central, 2011)
At birth, the immune system is still in development making neonates more susceptible to infections. The recognition of microbial ligands is a key step in the initiation of immune responses. It can be mimicked to stimulate the immune system by the use of synthetic ligands recognising pattern recognition receptors. In human and mouse, it has been found that neonatal cytokine responses to toll-like receptor (TLR) ligands differ in many ways from those of adults but the relevant studies have been limited to cord blood and spleen cells. In this study, we compared the responses in neonate and adult sheep to CpG oligodeoxynucleotides (ODN), a TLR9 ligand, in both a mucosal and a systemic organ. We observed that in response to CpG-ODN more IL-12 was produced by neonatal than adult sheep cells from mesenteric lymph nodes (MLN) and spleen. This higher IL-12 response was limited to the first 20 days after birth for MLN cells but persisted for a longer period for spleen cells. The major IL-12-producing cells were identified as CD14(+)CD11b(+). These cells were poor producers of IL-12 in response to direct stimulation with CpG-ODN and required the cooperation of other MLN cells. The difference in response to CpG-ODN between neonates and adults can be attributed to both a higher proportion of CD14(+)CD11b(+ )cells in neonate lambs and their higher capacity to produce IL-15. The IL-15 increases IL-12 production by an amplifying feedback loop involving CD40.